The Strategy of Price, Product, Promotion, and People Towards Efforts to Increase Sales at Pop Up Boutique - Gabriella Thie (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
Pop Up Boutique is a star up business in fashion industry that was established in 2020. At first, the business is going well as expected, but then Pop Up Boutique's revenue decreased drastically in 2022. The purpose of this research is to design a strategy of price, product, promotion, and people to increase sales, and hopefully the designed strategy can be applied in Pop Up Boutique. The method used is descriptive qualitative research method with direct observation, in-depth interviews and document review. 3 people were interviewed, 1 each from the management, customer, and expert. The interview results are translated into EFAS and IFAS analysis, then a SWOT analysis is made by determining the weight and rating, after that the SWOT matrix so that it can be seen which quadrant Pop Up Boutique is in, then a strategy can be determined according to the Pop-Up Boutique situation. The results of this study indicate that Pop Up Boutique is in Quadrant I (SO Strategy) which means it is in the Aggressive Strategy. This position indicates that Pop Up Boutique is in a good condition and has the opportunity to expand its business, by using all strengths to seize and taking advantage of opportunities in improving the company's progress. The strategy that will be implemented by Pop Up Boutique related to price is to determine the price based on cost-based pricing but also pay attention to competition-based pricing. Product strategy is to do positioning, product design, and differentiation. The promotion strategy carried out pays attention to promotional messages, promotional media, and time of promotion. People strategy is to set standardization in recruiting staff including competence, politeness, selective, communicative, appearance.